Conversations with Kenelm Essays on the Theology of the Commedia - Took, John (Ubiquity Press, 2013)
In a celebratory moment of the Paradiso, Dante has Thomas go round the circle of sage spirits identifying each in turn in point of proper calling and confirming how it is that self is everywhere present to the other-than-self as a co-efficient of being in the endless and endlessly varied instantiation of that being. The image, at once perfectly Dantean and perfectly resplendent, underlies and informs these conversations of mine with Kenelm; for if in reading and rereading the cherished text, I have from time to time felt the need to enter a qualification, it is a matter here, as in the high consistory of paradise, of otherness as both contained and as authorized by sameness, as conditioned and set free by it for a life of its own. Never, in other words, is it a question in what follows of the stark alternativism of the sed contra, but instead a matter of formed friendship, of the kind of friendship which, conceived in love, makes for a sweet choreography of the spirit. (DOI: 10.5334/baa)